Molecular diagnosis and intraspecific genetic variability of root pathogens of arid legumes in Western Rajasthan, India - Gautam, Ragini; Singh, S.K.; Sharma, Vinay (Revista de Biología Tropical, 2016)
The productivity of arid legumes, such as Clusterbean (Cyamopsis tetragonoloba), Cowpea (Vigna unguiculata), Moth bean (Vigna aconitifolia) and Horse gram (Macrotyloma uniflorum), may remain stagnant over decades because of their high susceptibility to root diseases. Besides, there is a limitation on the information about molecular diagnosis and intraspecific genetic variability of root pathogens in arid legumes. To contribute in this field, we assessed a total of 52 isolates from 88 root samples that were found infected with fungal pathogens in Jodhpur, Jaipur and Bikaner Districts of Rajasthan. Diseased roots samples were analyzed following standard microbiological methods for fungus extraction and purification, and for genetic studies. Irrespective of the geographical location from where the diseased samples were collected, all pathogen isolates were clustered in RAPD dendrograms as per their respective genera. Phylogram, based on multiple sequence alignment, revealed that different genera (i.e. Fusarium, Neocosmospora and Syncephalastrum), separated from each other, and species within the same genera, clustered together with their reference sequences with apreciable bootstrap values. Out of 20 representative isolates representing each cluster and all outgroups sequenced, eight were molecularly identified as Neocosmospora vasinfecta, five as Fusarium solani, two as Neocosmospora striata, two as Fusarium acutatum, one as Syncephalastrum monosporum, one as Fusarium oxysporum and one as Fusarium species. The root pathogens of the arid legumes were found neither restricted to a geographical location nor were host specific in nature. Fusarium solani wilt in cowpea and seedling rot in moth bean, F. oxysporum wilt in moth bean, F. acutatum damping off in cowpea and Clusterbean, Fusarium sp. seedling rot in Clusterbean, Neocosmospora striata root rot in cowpea and wilt in Clusterbean and Syncephalastrum monosporum root rot in Clusterbean were molecularly identified as new fungal records as pathogens causing root diseases in arid legumes.